2015
DOI: 10.1186/s12891-015-0549-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported quality of life, anxiety and depression in individuals with Ehlers-Danlos syndrome (EDS): a questionnaire study

Abstract: BackgroundMany individuals with Ehlers-Danlos Syndrome (EDS) are hypermobile, suffer from long term pain, and have complex health problems. Since these sometimes have no objective physical signs, individuals with EDS sometimes are referred for psychiatric evaluation. The aim was therefore to identify the level of anxiety and quality of life in a Swedish group of individuals with EDS.MethodsA postal survey in 2008 was distributed to 365 members over 18 years of the Swedish National EDS Association and 250 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 16 publications
7
48
1
3
Order By: Relevance
“…The high proportion of females in our registry databases is consistent with proportions reported by other EDS registers9–11 30 but ultimately may be considered as a limitation when it comes to the generalisability of the data.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The high proportion of females in our registry databases is consistent with proportions reported by other EDS registers9–11 30 but ultimately may be considered as a limitation when it comes to the generalisability of the data.…”
Section: Discussionsupporting
confidence: 81%
“…Our data also suggest that OSA has a role in the development of fatigue, daytime sleepiness and impaired quality of life in patients with EDS. A large body of evidence has documented that these symptoms represent significant problems in day-to-day life in the EDS population 9 10 30. High-quality data about adverse effects of OSA in EDS are clinically crucial, because OSA is treatable and its therapy has been shown to effectively reduce daytime sleepiness, to increase quality of life and to successfully prevent other adverse consequences 31–33…”
Section: Discussionmentioning
confidence: 99%
“…Based on a review of titles and abstracts we found six papers 35,38,[91][92][93][94] reporting generic health-related quality of life in patients with JHS (Table 31). These studies typically were cross-sectional surveys with small numbers of patients with JHS (range 20-115).…”
Section: Previous Relevant Literature To Inform the Value-of-informatmentioning
confidence: 99%
“…The correlation of kinesiophobia with the severity of fatigue is strong (Celletti, Castori, La Torre, & Camerota, ) and is reflected in decision‐making processes with regard to pain and activity (Schmidt, Corcoran, Grahame, & de‐C‐Williams, ). Quality of life in these patients is often reduced because of chronic pain (Berglund, Pettersson, Pigg, & Kristiansson, ; Murray et al, ; Rombaut et al, ). Functional impairment in patients with JHS/EDS‐HT is similar to that in fibromyalgia (FMS) sufferers, and significantly worse than in patients with rheumatoid arthritis (Rombaut et al, ).…”
Section: Introductionmentioning
confidence: 99%